Principles of Catholic theology. - White, Thomas Joseph, 1971- (Thomistic ressourcement series, 2023)
"Catholic theology has to ask and answer fundamental questions: what is the nature and content of Christian revelation, what are the sources of revelation, how are the mysteries of the faith to be understood in relation to one another, and how do the truths of the Catholic faith relate to those of natural reason. In this four book set within the larger Thomistic Ressourcement series, Thomas Joseph White answers these fundamental questions and discusses the central mysteries of faith as they relate to God and human beings. Book 1 is a set of essays about the task of Catholic theology from a Thomistic point of view. Book 2 is an argument for the reasonableness of Christianity in a secular and pluralistic age. Book 3 is a set of essays on Trinitarian, Christological, and creation theology. Book 4 is a set of essays on theological anthopology, including Mariology and ecclesiology"--